Far-red emission of CaYAlO4:Mn4+ synthesized by co-precipitation method - Duong, L. Q.; Quang, N. V.; Nguyen, D. H. (Vietnam Journal of Science and Technology, 2020)
Light absorption of the most plants is in range of blue (440 nm), deep-red (660 nm) and far-red around 700-740 nm. The deep-red and far-red light plays important roles in reactions of photomorphogenesis of plants. Although red emission phosphors have been researched extensively for white light-emitting diodes, deep-red and far-red emission phosphors for plant growth have been reported inadequately. Thus, in this work, far-red emitting CaYAlO4:Mn4+ phosphor was synthesized by co-precipitation method coupled with various annealing temperature from 800oC to 1300oC for 5 h. The crystal structure, morphology, and photoluminescence properties of CaYAlO4:Mn4+ phosphors were investigated in detail. The crystallinity of the phosphor belongs to tetragonal system with space group I4/mmm. Y3+ and Ca2+ ions are coordinated by nine oxygen atoms to form [YO9] and [CaO9] polyhedrons, and the Al3+ ions are coordinated by six oxygen atoms forming [AlO6] octahedrons that provided suitable sites for Mn4+ ions. The obtained sample showed an irregular surface morphology with micro size particles. Under the excitation of 320 nm, CaYAlO4:Mn4+ phosphors gave bright far-red emission around 710 nm due to the 2Eg→4A2g transition of Mn4+ ions. The critical concentration of Mn4+ doped in CaYAlO4 host lattice is 0.5 mol.%. The results show that the CaYAlO4:Mn4+ phosphors may be applied to indoor plant growth illumination.